Liquid Chromatography Mass Spectrometry (LC-MS) Fingerprint Combined with Chemometrics for Identification of Metabolites Content and Biological Activities of Curcuma aeruginosa - Dewi Anggraini Septaningsih; Latifah Kosim Darusman; Farit Mochamad Afendi; Rudi Heryanto (Universitas Gadjah Mada, 2018)
Curcuma aeruginosa is known as one of the components of herbal medicine with various biological activities. This research aims to identify the metabolites content of C. aeruginosa related to their biological activities using LC-MS fingerprint combined with chemometrics. C. aeruginosa from 3 areas in Java were collected and macerated with ethanol and then analyzed with LC-MS. Along with this analysis, the antioxidant activity of all samples was determined using CUPRAC method, and the toxicity was determined using Brine Shrimp Lethality Test (BSLT), and chemometric method was used Principle Component Analysis (PCA) and Partial Least square (PLS). Metabolites profiles showed 175 predicted compounds, in which the dominant compounds are from the sesquiterpene of Curcuma genus. The PCA metabolites profiles can separate the samples by their location of origin. Interpretation of the correlation between metabolites profiles and their bioactivities was determined using PLS technique. The results showed that the toxicity of samples was exerted by compounds with ion mass of 312.28 and 248.15, which have the highest antioxidant and toxicity potentials. Compounds with ion mass of 248.15 were predicted to be 9-Oxo-neoprocurcumenol, 7α,11α,-Epoxy-5β-hydroxy-9-guaiaen-8-one, Curcumenolactone A, or Curcumenolactone B. While compound with ion mass of 312.28 was predicted to tetrahydro-bisdemethoxycurcumin.